Using biographical methods in social research - Merrill, Barbara; West, Linden (Sage Publications, 2009)
The book's pedagogical features, practical focus and cross disciplinary theoretical perspective makes this an interesting, accessible and interactive as well as a provocative textbook for students and researchers.